Implementasi Model Project-Based Learning dalam Kurikulum Merdeka Bagi Guru Sekolah Dasar - Anggit Grahito Wicaksono; Ifa Hanifa Rahman (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Merdeka curriculum has a focus on the quality of learning rather than quantity. The Merdeka curriculum focuses on a project-based learning model. Based on interviews and observations with elementary school teachers in Selo, Boyolali, most admitted that they had not been able to understand, and implement the project-based learning (PjBL) model in the Merdeka curriculum and that most teachers had not been able to make Proyek Penguatan Profil Pelajar Pancasila using project-based learning models. The goal to be achieved from this service program is to provide understanding and skills in implementing project-based learning models in the independent curriculum. The method of implementing the service includes (1) the approach method which is carried out starting from the survey, licensing, and motivational stages for teachers who will take part in the training (2) the method of implementing the program, including the preliminary stage, the socialization and audience stages, the implementation stage, and the final evaluation stage. The results of the analysis show that there is an increase in the teacher's ability to understand the project-based learning model in the Merdeka curriculum. The pretest and posttest scores showed an increase from 43.43 to 70.86. In addition, 35 teachers attended and successfully implemented the model, exceeding the set target. Teachers also gave positive responses to training on the implementation of the project-based learning model, which they considered to be very much needed in the development of an Merdeka curriculum. They feel the benefits of community service activities because they can increase their scientific insights and learn at school.